Cultivating Knowledge and Skills to Grow African Agriculture - Agwe, Jonathan (World Bank, Washington, DC, 2012)
This Program states that larger investments in agricultural research, extension, and education systems are required to achieve the targeted increase in agricultural output of 6 percent a year over the next 20 years.To enhance the quality and productivity of Agricultural Education and Training (AET) in Africa, the case for improving its agricultural education capacities is compelling in view of their seminal role in agricultural development elsewhere in the world. AET development was an integral part of strategies of countries that grew agriculture successfully, such as Brazil, India, and Malaysia. The analytical work carried out on AET in Africa identified some priorities as key to modernize agricultural education in Africa These priorities are: 1 Political will must be generated in support of agricultural development by educating the public about its role in economic growth and poverty reduction, creating capacities for lobbying, joining forces with other stakeholders, and sustaining these efforts over two or three decades.(2) It is desirable to assess and re-balance AET enrollment profiles away from secondary level vocational training towards diploma, degree, and post-graduate levels (3) It is essential to replenish human capital by strengthening and expanding national Master of Science programs, laying the foundation for Ph.D. programs, and tackling the conundrum of incentives for staff retention.(4) Finances must be managed proactively by making more efficient use of existing resources, mobilizing non-public resources, and persuading donors to finance operating costs.(5) Much better gender balance must be achieved among AET graduates. African universities and other institutions of higher learning ultimately will be responsible for replenishing the stock of human capital in national research and extension services, and for providing them with the broader set of skills necessary to grow agriculture in the 21st century.